Radial Probe Endobronchial Ultrasound and Novel Navigation Biopsy Techniques - Chenna, Praveen; Chen, Alexander C. (Seminars in Respiratory and Critical Care Medicine, 2014)
Peripheral pulmonary lesions are an increasingly common finding in clinical practice. While many nodules are followed with radiographic surveillance, some may require biopsy. Conventional bronchoscopy with transbronchial lung biopsy has traditionally performed poorly for small, peripheral lesions, and transthoracic needle aspiration with computed tomographic (CT) guidance has been favored as the diagnostic test of choice. Despite the high diagnostic yield of transthoracic needle aspiration, procedural complications such as pneumothorax continue to be problematic. New technology has been developed to improve the diagnostic yield of bronchoscopy for peripheral lesions over conventional methods, while maintaining the favorable safety profile of a bronchoscopic approach. Virtual bronchoscopy and electromagnetic navigation are CT-based image guidance systems that create virtual bronchoscopic representations of the tracheobronchial tree to assist the bronchoscopist in locating peripheral lesions. Radial probe endobronchial ultrasound utilizes real-time ultrasound to confirm the location of peripheral lesions before biopsy. This article summarizes the technical platforms, procedures, and clinical evidence for these emerging technologies.
Keywords: bronchoscopy; pulmonary nodule; virtual bronchoscopy; electromagnetic navigation; endobronchial ultrasound